2004
DOI: 10.1080/08957950310001635828
|View full text |Cite
|
Sign up to set email alerts
|

Biology under extreme conditions

Abstract: The conditions for temperature and pressure survival of organisms point to proteins as the primary target. The elliptic shape of the stability phase diagram of proteins in aqueous solutions suggests that hydration and packing specificity are important factors. Pressure is a valuable tool for the study of partially unfolded protein conformations that give rise to aggregation and fibril formation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 61 publications
0
4
0
Order By: Relevance
“…Moreover, high pressure can induce unfolding of protein in a different way from thermal denaturation . The pressure studies have considerably increased in the past decade. , …”
Section: Pressure and Temperature Unfolding Of Proteinsmentioning
confidence: 99%
“…Moreover, high pressure can induce unfolding of protein in a different way from thermal denaturation . The pressure studies have considerably increased in the past decade. , …”
Section: Pressure and Temperature Unfolding Of Proteinsmentioning
confidence: 99%
“…The mechanistic aspects underlying this phenomenon, called pressure-induced thermostabilization, are still elusive. Hei and Clark [43] suggested that the stabilization is correlated with the hydrophobicity of the protein, whereas Heremans [44] suggested a link with aggregation. Here, we have shown that pressure stabilizes myoglobin against temperatureinduced denaturation and concomitant aggregation.…”
mentioning
confidence: 99%
“…Although canonical DNA duplexes are stabilized by pressure, DNA-protein interactions may be perturbed due to changes in the electrostatic and hydrophobic interactions. Accordingly, pressure affects negatively all molecular reactions where DNA is involved, such as replication, transcription and recombination [28,29].…”
Section: Nucleic Acidsmentioning
confidence: 99%